On the role of key players in rural social innovation processes - Ralph Richter; Gabriela B. Christmann (Journal of Rural Studies, 2021)
Social innovation (SI) research tends to understand rural SI processes as collective initiatives of equally engaged, supportive, and like-minded people. However, recent research has indicated that SI projects often benefit from dedicated key players who find support in their communities but also must deal with resistance and barriers. Against this backdrop, this article explores the figure of the key player in SI research and exposes the patterns of rural SI processes with the empirical cases of two small communities in Germany that jointly created rural infrastructure systems, thus seeking emancipation from remote political and economic control and marginalization. Using the empirical cases, we tested and specified a heuristic framework of key players that combines analytical dimensions at the micro-, meso-, and macro-levels. According to our findings, the heuristic framework is appropriate for analyzing key players in rural SI processes. Notably, we show that SI processes benefit from assertive key players and strong communities capable of joint action. Both are crucial for dealing with internal opposition and overcoming external hurdles that appear when novel approaches irritate familiar solutions and routines.
Keywords: 710; Key player; Social innovation process; Rural community; Social emancipation; Embedded intermediary